(untitled) (The Pakistan Development Review, 2008)
The role of foreign aid in promoting economic growth is a debatable issue and remains unsettled at both theoretical and empirical levels. Pakistan has received a substantial amount of foreign aid since its Independence in 1947 but little improvement has been observed in its socio-economic development. This study considers the question as to whether foreign aid is a blessing or a curse for Pakistan. The empirical analysis is based on the ARDL cointegration approach. We examine the aid-growth link at the aggregate and disaggregate levels for the period 1972-2006. The results show negative and insignificant effects of foreign aid on the growth at the aggregate as well at the disaggregate level. The findings further suggest that domestic investment, export growth, and inflows of foreign direct investment are important contributors in enhancing economic growth in Pakistan. JEL classification: C13, C22, F23, F35, O11 Keywords: Foreign Aid, Economic Growth, FDI, Cointegration